MARKETING STUDIES OF LOCAL MARKET OF DRUGS WHICH ARE APPLIED FOR PREVENTION AND TREATMENT OF ORAL CAVITY DISEASES - O. A. Tsarakhov; L. N. Tsarakhova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
Stomatological market has actively developed recent years. Domestic experts received an access to contemporary technologies of dental diseases treatment in the world. This conditioned the appearance of new drugs and parapharmaceutical products applied in dental practice on the pharmaceutical market. In this connection, study of these drugs market, their price policy, demand and supply. Assortment of parapharmaceutical products applied in dental practice for oral cavity hygiene is represented mainly by liquid forms, such as mouth rinse, balms, elixirs, and a special place is occupied by toothpastes. Their assortment amounts to more than 700 types. Drugs, applied in dental practice are represented by the following groups: anti-inflammatory, antimicrobial, antiallergenic, anesthetics, drugs which stimulate tissues regeneration, fluoric drugs. The purpose of this study was the analysis of regional pharmaceutical market assortment, which offers parapharmaceutical goods and drugs for prevention and treatment of oral cavity diseases to the stomatological establishments. Pharmaceutical market of the Republic of North Ossetia - Alania is represented by a wide range of drugs for dental diseases treatment. This group is represented in the assortment of practically all distributors. The drugs for dental diseases treatment is not only supplied by domestic producers but also go from pharmaceutical companies of 29 foreign countries, which influences positively on the state of drug therapy of paradontum in the region.